(untitled) (Mustansiria Dental Journal, 2019)
Aim: The objectives of this study are to compare and evaluate under standardized experimental conditions the centering ability (centering ratio) and canal transportation (outer and inner transportations) of three NiTi instruments ProtaperNext files (Dentsply Maillefer), XP-endo shaper (XP; FKG Dentaire, La Chaux-de-Fonds, Switzerland), Waveone Gold files (PTG; Dentsply Tulsa Dental Specialties), in simulated curved canals of 40° curvature at different levels. Methods: 60 Readymade simulated curved canals made of clear polyester resin (DENTSPLY Maillefer ,Ballaigues,Switzerland) will be used in this study were randomly assigned to 3 experimental groups (n = 20). In the Waveone Gold and PTN the first preparation in the simulated canals will perform with # 10 K-file to full working length (16mm) while for XP-Shaper canals will perform with # 15 K-file. Prior to their preparation, each simulated canal will fill with a drawing ink using a 27 gauge needle to enhance photographic contrast. Photographs of prepared and unprepared canals will be taken by the aid of stereomicroscope and digital camera at magnification of 40 times. Results: the XP Shaper system that preserved the best rate of shaping among the inner/outer walls over the total length of the simulated curved canals (i.e. values closest to 0) than that of the ProTaper NEXT and WaveOne Gold instruments. Conclusion: The XP-shaper group showed less canal transportation and better centering ability than ProTaper Next and WaveOne Gold groups at all the five measuring levels, The WaveOne Gold group showed less outer canal transportation at the beginning and the apex of the curve, and better centering ability than ProTaper Next group at all the five measuring levels, ProTaper Next group showed less inner transportation at the end of preparation, while WaveOne Gold is better in the middle part (half – way levels & beginning of the curve) & the least centering ability at all the five measuring levels.